ELECTRE ME: a proposal of an outranking modeling in situations with several evaluators - Costa, Helder Gomes; Nepomuceno, Livia Dias De Oliveira; Pereira, Valdecy (Brazilian Journal of Operations & Production Management, 2018)
Highlights: This paper describes an original proposal for modeling Multicriteria problems taking into account more than one evaluator. It allows each evaluator to have its own set of criteria. It also avoids the incoherency of adopting compensatory techniques into non-compensatory algorithms. Goal: This paper describes an original proposal for modeling multicriteria situations where multiple evaluators take part of the evaluation process. This proposal allows each evaluator to have its own set of criteria, including their weights, and also avoids the usual inconsistency of adopting pre-processing compensatory methods for introducing it into non-compensatory algorithms. Design / Methodology / Approach: In order to better describe how ELECTRE ME works, a multicriteria-multiple evaluator situation is modeled by ELECTRE TRI ME (as we have called the ELECTRE TRI variation that incorporates the principles of multiple evaluators). Results: ELECTRE ME was able to avoid the inconsistency of adopting contradictory mechanisms of aggregating preferences while modeling multicriteria & multiple evaluators problems (first called here as MCDA-ME). Limitations: Although the proposal focuses in situations with multiple evaluators, there is no restriction for its application in situations where there is only one decision maker. Practical implications: Another important feature of ELECTRE ME is that it allows each evaluator to consider its own set of criteria and its own scale for evaluation. Originality / Value: ELECTRE ME avoids a contradictory approach to use compensatory algorithms (such as weighted mean) as an input in non-compensatory outranking methods. Despite the fact that non-compensatory principle is in the heart of the ELECTRE methods, it has not found a previous proposal with the attributes shown in this study: to incorporate outranking concepts in situations where more than one evaluator is present and, by extension, allow each evaluator to have its own set of criteria.